CAD OF A THREE ELELCTRODE ELECTROSTATIC IMERRSION LENSES USING THE SPLINE MODEL - Ahmad, Ahmad Kamal (Al-Nahrain Journal of Science, 2018)
The focal properties and aberrations for three electrode electrostatic lenses are investigated indetail using the two-interval spline lens model. The synthesis procedure of optimization has beentaken into account with the aid of the spline function. The potential ratio is investigated as aneffective parameter in lens design.The optimization procedure has shown the possibility of obtaining a practical design ofelectrostatic lenses operated under pre-assigned conditions to yield minimum aberrations.Non-relativistic velocities and neglecting the space-charge effects are the two main assumptionsthat have been taken into account throughout the work. The actual electrodes profile which isdetermined from equipotential surfaces has been constructed in three-dimensional diagrams.